2010
DOI: 10.1021/jp108059x
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Predictions of the Temperature-Dependent Viscosities and Electrical Conductivities of Functionalized and Nonfunctionalized Ionic Liquids

Abstract: The viscosity (η) and electrical conductivity (κ) of ionic liquids are, next to the melting point, the two key properties of general interest. The knowledge of temperature-dependent η and κ data before their first synthesis would permit a much more target-oriented development of ionic liquids. We present in this work a novel approach to predict the viscosity and electrical conductivity of an ionic liquid without further input of experimental data. For the viscosity, only some basic physical observables like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 75 publications
2
93
0
Order By: Relevance
“…Normally, ionic liquids based on imidazolium cations show conductivities in the range of 1 to 10 mS cm −1 at 25 • C [18,19]. In line with this observation the compound under investigation also exhibits an exceptionally high conductivity of, e. g., 52.1 mS cm −1 at 25.6 • C. Like for other ILs the temperature dependence of the conductivity is well described by a VogelFulcher-Tammann behavior [18].…”
Section: Conductivitysupporting
confidence: 59%
“…Normally, ionic liquids based on imidazolium cations show conductivities in the range of 1 to 10 mS cm −1 at 25 • C [18,19]. In line with this observation the compound under investigation also exhibits an exceptionally high conductivity of, e. g., 52.1 mS cm −1 at 25.6 • C. Like for other ILs the temperature dependence of the conductivity is well described by a VogelFulcher-Tammann behavior [18].…”
Section: Conductivitysupporting
confidence: 59%
“…4 ]-based ILs with V m,scaled . [58] As seen in Figure 1 a, Equation (2) As a further test T dependent values of h were fitted according to Equation (3): [59] …”
Section: Volume-based Correlationsmentioning
confidence: 99%
“…These are unity for almost all ions with the exception of those with tetrahedral (s À = 12) and octahedral (s À = 24) symmetry. Compared to the originally used formula, [59] the molecular radius r m in the second term is replaced by the volume V i . It is calculated as the sum of the constituting ion volumes.…”
Section: Dg*mentioning
confidence: 99%
“…Several recent studies showed that this is possible, for example, for conductivity, viscosity, density, surface tension and refractive index. [22][23][24][25] In continuation of our earlier work on IL properties, [23,[26][27][28][29][30][31][32][33] this manuscript is devoted to promote a further understanding and prediction of the detailed temperature-dependent viscosities and conductivities of ILs. Therefore, we first review in some detail the fundamentals of viscosity and conductivity, since they are important for the discussions below.…”
Section: Introductionmentioning
confidence: 99%